DAMPAK PEMBELAJARAN INKUIRI BERJENJANG DALAM MENINGKATKAN KETERAMPILAN MENULIS ARGUMENTATIF CALON GURU (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2015)
The purpose of this study was to evaluate biology teacher candidates’s argumentative writing skill after they participated in hierarchy of inquiry learning.  The participants of this  action research are the 4th semester students of  Biology Teacher Education Program Faculty of Teacher Training and Education Sebelas Maret University  who took the course of Plant Embryology.  Data were analyzed descriptively through interviews with experts, classroom observations, and student portfolios. The argumentative writing was measured using Toulmin’s Argument Pattern (TAP) with four kinds of argument elements, which include data, warrants, backings, and claims. The results showed that the argumentative writing skill was increased, in every aspect and levels of inquiry.  Biology teacher candidates who had well-experienced in the hierarchy of inquiry outperformed argumentative writing skill, thus it can be concluded that   Hierarchy of Inquiry Learning is suitable in fostering teacher candidates to do some inquiry activities, and positively impacted  argumentative writing skill.    Penelitian ini dilakukan dengan tujuan untuk mengevaluasi kemampuan menulis argumentatif calon guru biologi meningkat  setelah mereka mendapatkan pembelajaran inkuiri berjenjang.  Partisipan dalam penelitian tindakan kelas ini adalah mahasiswa semester 4 di Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta yang menempuh mata kuliah Embriologi Tumbuhan.  Data dianalisis secara deskriptif melalui wawancara, pengamatan kelas dan portofolio.  Kemampuan menulis  diukur menggunakan Toulmin’s Argument Pattern (TAP) yang meliputi empat komponen, yaitu data, warrants, backings, dan claims.   Hasil penelitian menunjukkan bahwa pada akhir siklus kedua terjadi peningkatan skor keterampilan berpikir argumentatif pada setiap aspeknya  di semua tingkatan jenjang inkuiri.  Calon guru biologi yang telah berpengalaman dalam inkuiri berjenjang menunjukkan kemampuan menulis argumentasi yang lebih baik sehingga disimpulkan bahwa  pembelajaran dengan inkuiri berjenjang sesuai diterapkan untuk mendukung berbagai aktivitas inkuiri  dan  meningkatkan kemampuan menulis argumentatif.
Keywords: calon guru biologi; inkuiri berjenjang; tulisan argumentatif; argumentative writing; pre-service biology teachers; hierarchy of inquiry